2012
DOI: 10.5617/nordina.415
|View full text |Cite
|
Sign up to set email alerts
|

Reading Nature- experienced teachers’ reflections on a teaching sequence in ecology: implications for future teacher training

Abstract: Ola Magntorn is a lecturer in biology and geology at Kristianstad University. He has a teacher education for upper secondary school and he has worked as a teacher in both compulsory school and upper secondary school. Since 2002 he is associated to the national graduate school in science and technology education (FontD) at Linköping University. His main focus of research is on ecology education and the ability to read nature.Gustav Helldén is a professor of science education at Kristianstad University. He has l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…There was acknowledgement that use of a local habitat reduced difficulties related to risk assessment and adult:child ratios. A similar issue was reported by Magntorn and Helldén (2006), who found that a lack of 'high quality nature' was the second most common issue raised by teachers who were attempting to explain the reasons that their colleagues did not engage in fieldwork. The same teachers did not see this as an issue in their own practice, perhaps linked to their confidence in their own experience (see above).…”
Section: Practising Teachers' Perceptionsmentioning
confidence: 54%
See 4 more Smart Citations
“…There was acknowledgement that use of a local habitat reduced difficulties related to risk assessment and adult:child ratios. A similar issue was reported by Magntorn and Helldén (2006), who found that a lack of 'high quality nature' was the second most common issue raised by teachers who were attempting to explain the reasons that their colleagues did not engage in fieldwork. The same teachers did not see this as an issue in their own practice, perhaps linked to their confidence in their own experience (see above).…”
Section: Practising Teachers' Perceptionsmentioning
confidence: 54%
“…Subject knowledge per se was not considered to be a significant barrier and teachers described themselves as being equipped to overcome the knowledge barrier if they have the confidence and motivation to do so. Magntorn and Helldén (2006) reported that a sample of experienced teachers in Sweden held a similar view about themselves but believed that a lack of subject confidence did prevent their colleagues from carrying out fieldwork. It is likely that having a combination of practical and subject experience will enhance an individual teacher's willingness to step outside.…”
Section: Practising Teachers' Perceptionsmentioning
confidence: 94%
See 3 more Smart Citations